Different Transcriptional Responses from Slow and Fast Growth Rate Strains of Listeria monocytogenes Adapted to Low Temperature - Cordero, Ninoska; Maza, Felipe; Navea-Perez, Helen; Aravena, Andrés; Marquez-Fontt, Bárbara; Navarrete, Paola; Figueroa, Guillermo; González, Mauricio; Latorre, Mauricio; Reyes-Jara, Angélica (Frontiers in Microbiology, 2016)
Listeria monocytogenes has become one of the principal foodborne pathogens worldwide. The capacity of this bacterium to grow at low temperatures has opened an interesting field of study in terms of the identification and classification of new strains of L. monocytogenes with different growth capacities at low temperatures. We determined the growth rate at 8 ºC of 110 strains of L. monocytogenes isolated from different food matrices. We identified a group of slow and fast strains according to their growth rate at 8 °C and performed a global transcriptomic assay in strains previously adapted to low temperature. We then identified shared and specific transcriptional mechanisms, metabolic and cellular processes of both groups; bacterial motility was the principal process capable of differentiating the adaptation capacity of L. monocytogenes strains with different ranges of tolerance to low temperatures. Strains belonging to the fast group were less motile, which may allow these strains to achieve a greater rate of proliferation at low temperature.